Pushing the limits : a very compact and a threshold implementation of AES - Moradi, Amir (2012)
Our contribution is twofold: first we describe a very compact hardware implementation of AES-128, which requires only 2400 GE. This is to the best of our knowledge the smallest implementation reported so far. Then we apply the threshold countermeasure by Nikova et al. to the AES S-box and yield an implementation of the AES improving the level of resistance against first-order side-channel attacks. Our experimental results on real-world power traces show that although our implementation provides additional security, it is still susceptible to some sophisticated attacks having enough number of measurements.